Extrusion and Microfluidic‐Based Bioprinting to Fabricate Biomimetic Tissues and Organs. Issue 8 (26th May 2020) - Davoodi, Elham; Sarikhani, Einollah; Montazerian, Hossein; Ahadian, Samad; Costantini, Marco; Swieszkowski, Wojciech; Willerth, Stephanie Michelle; Walus, Konrad; Mofidfar, Mohammad; Toyserkani, Ehsan; Khademhosseini, Ali; Ashammakhi, Nureddin
Abstract: Next generation engineered tissue constructs with complex and ordered architectures aim to better mimic the native tissue structures, largely due to advances in 3D bioprinting techniques. Extrusion bioprinting has drawn tremendous attention due to its widespread availability, cost‐effectiveness, simplicity, and its facile and rapid processing. However, poor printing resolution and low speed have limited its fidelity and clinical implementation. To circumvent the downsides associated with extrusion printing, microfluidic technologies are increasingly being implemented in 3D bioprinting for engineering living constructs. These technologies enable biofabrication of heterogeneous biomimetic structures made of different types of cells, biomaterials, and biomolecules. Microfluiding bioprinting technology enables highly controlled fabrication of 3D constructs in high resolutions and it has been shown to be useful for building tubular structures and vascularized constructs, which may promote the survival and integration of implanted engineered tissues. Although this field is currently in its early development and the number of bioprinted implants is limited, it is envisioned that it will have a major impact on the production of customized clinical‐grade tissue constructs. Further studies are, however, needed to fully demonstrate the effectiveness of the technology in the lab and its translation to the clinic. Abstract : Extrusion bioprinting is introduced and the applications, limitations, and recent advances are discussed. Furthermore, the integration of microfluidic technologies with extrusion bioprinting for controlled biofabrication of 3D constructs to better mimic human tissue is outlined. Although the field is still developing, it is envisioned that it can have a huge impact on biofabrication of customized heterogeneous 3D tissues in near future.